Health education and the quality of life in children suffering from bronchial asthma - Trojanowska, Alina; Emeryk, Andrzej (Polish Journal of Public Health, 2009)
Introduction. Bronchial asthma has been an increasing health problem of modern society. Among many threats that asthma creates, there is a deterioration in the quality of life associated with regular administration of medicines, with side effects related with the treatment and life threatening incidents associated with exacerbation of the symptoms. Many research reports emphasize the importance of health education in improving the quality of life of the patients. Purpose of study. The purpose of study was to evaluate infl uence of the level of knowledge of asthma and healthpromoting behaviors on the quality of life of children suffering from bronchial asthma. Material and methods. The subjects of the study were 100 children with chronic bronchial asthma treated at outpatient pulmonological departments of Children’s University Hospital in Lublin. The PAQLQ survey, the test of knowledge about asthma designed for the purpose of the study and the analysis of medical records, were the research tools. The material was used to evaluate the level of children’s knowledge about asthma, identify deficits in certain fields and self-control skills. Results. The statistical analysis confirmed a significant infl uence of the level of knowledge on emotional functions of the examined children (p=0.005). It turned out that with the increase of knowledge, the respondents less frequently expressed negative emotions associated with the disease, such as fear, anxiety, worry, dissatisfaction or nervousness. Children with high level of knowledge seldom reported the feeling of lower value, being different or outcast from their environment in comparison to others. The analysis of the table reveals that sick children are not able to keep self-control charts successfully, monitor the course of asthma with the use of pickfl owmeter or prevent, identify and cope with exacerbation. Statistical analysis revealed significantly lower quality of life among the children with mastered skills to selfcontrol the disease in comparison to others (p=0.033). Conclusions. High level of knowledge of the patients about the disease positively infl uenced children’s emotions; however self-control of asthma reduced children’s daily activities. The study confirmed the necessity of including health education into complex therapeutic – nursing management of the disease.